1281. Longitudinal and Spatial Variation in the Human Microbiome in a Phase 2a Clinical Study of Gepotidacin in Adult Females with Uncomplicated Urinary Tract Infection. (31st December 2020) - Nuzzo, Andrea; Van Horn, Stephanie; Traini, Christopher; Perry, Caroline R; Dumont, Etienne; Scangarella-Oman, Nicole; Gardiner, David; Brown, James R
Abstract: Background: Gepotidacin (GSK2140944) is a first in class novel oral triazaacenaphthylene bacterial topoisomerase inhibitor. In this study, we evaluated the potential impact of orally administered gepotidacin on the human microbiome, across three body-sites and at three specific time-points, as an exploratory endpoint in a Phase 2a clinical trial for the treatment of uncomplicated Urinary Tract Infection (uUTI) (ClinicalTrials.gov: NCT03568942). Methods: Through DNA sequencing of the 16S rRNA variable region 4, we analyzed samples collected with consent from study subjects from the gastrointestinal tract or GIT (stool), pharyngeal cavity (saliva swabs) and vagina (vaginal swabs). Samples were taken at three time points which were pre-dosing (Day 1), end of dosing (Day 5) and follow-up visit (Day 28 ±3 days). A total of 156 samples were collected and 141 samples passed quality control criteria for DNA sequence analyses. Using a rigorous computational work-flow, changes in microbiome diversity and relative abundances of microbial species were quantified. Results: Time series analyses showed that microbiota alpha diversity dropped, relative to pre-dose, by the end of gepotidacin dosing but trended a return trajectory to original pre-dose levels by the follow-up visit, for all body sites (Figure). However, the character and extent of the microbiota changes varied by location. The relative ordering from least to greatest changes in microbiota diversity of body sites is vaginal, pharyngeal and GIT. We found no statistically significant occurrences of pathogen related taxa, such as Clostridioides or Enterobacterales spp., at the final timepoints. Conclusion: Since gepotidacin is both orally dosed and elimination includes the biliary route, it was predicted to affect the GIT microbiome, however changes in the distal pharyngeal and vaginal microbiota were also observed. Gepotidacin alteration of the endogenous microbial community appears to be temporary and reversible as microbiota diversity rebounded to near pre-dosing status within a period of several weeks. Our study illustrates how microbiome analyses in antibiotic clinical studies can quantify patterns of microbiota disruption and recovery. Disclosures: Andrea Nuzzo, PHD, GlaxoSmithKline (Employee) Stephanie Van Horn, B.Sc., GlaxoSmithKline (Employee) Christopher Traini, PHD, GlaxoSmithKline (Employee) Caroline R. Perry, PhD, GlaxoSmithKline (Employee) Etienne Dumont, MD, GlaxoSmithKline (Employee) Nicole Scangarella-Oman, MS, GlaxoSmithKline plc. (Employee, Shareholder) David Gardiner, MD, GlaxoSmithKline (Employee) James R. Brown, PhD, GlaxoSmithKline (Employee)